PHENOTYPIC FEATURES OF ENDOMETRIAL CANCER AND MSI IN COLON AND BLOOD SERUM - S. M. Kartashov; E. M. Oleshko (Zaporozhye State Medical University, 2014)
Since the end of the last century an upward trend regarding hormone-dependent tumours of the reproductive system, including endometrial cancer (EC) has been observed, with one of the trend reasons being increased number of mutations, in particular, microsatellite instability (MSI) - the consequence of unpaired nucleotides repair system gene inactivation (MSH2, MSH3, MSH6, MLH1,PMS2, EXO1). This molecular genetic phenomenon may also be characteristic of certain colon cancer forms, while being detectable not only in the tumour but also in blood, which may be of clinical interest as regards either determining risk groups in terms of other localization malignant tumours development, especially colon cancer, or early diagnostics of the said diseases. However, relationship between clinical, phenotypic and molecular risk factors for EC and colon cancer needs further studying. The aim of research - to estimate MSI frequency in blood serum and colonic mucosal lining in patients with EC. Materials and methods. 342 patients with I - IV stage EC aged between 30 and 80 underwent MSI determining in tumour tissue, blood serum and colonic mucosa by means of polymerase chain reaction method using primers for microsatellite sequence (ВАТ-25, ВАТ-26). Colonic mucosal lining samples were obtained by colonoscopy prior to surgical intervention. Genomic DNA purification from blood serum was performed using DNA purification kit produced by Silex M Scientific and Production Company (Russia), in accordance with manufacturer's instructions. PCR was performed by the standard procedure using Tertsik-2 programmable thermal cycler produced by DNA - Technology LTD, Russia. The studies were carried out at Virola laboratory at Kharkiv Medical Academy of Postgraduate Education. Ethics and Bioethics Committee permit (minutes No.4 of 18.04.2013, Kharkiv Medical Academy of Postgraduate Education). The obtained digital study results were processed by means of conventional variation statistics methods using the χ2 criterion. Results. Estimation of MSI occurrence frequency in the colon tissue showed that MSI- colonic tissue is significantly more frequent (93.9 %) compared to MSI+ (6.1 %), p<0.01. Analysis of MSI occurrence frequency in case of EC showed that MSI is significantly more frequently observed in blood serum (10.8 % of cases) than in the colonic tissue (mucosal lining) (6.1 %). A similar pattern was observed also in cases with MSI+ tumour phenotype (MSI frequency in colonic mucosal lining made 12.2 %, whereas in blood serum - 29.6 %, p <0.01). Analysis of indices in cases with MSI- tumour phenotype demonstrated inverse relation, i.e. genome microsatellite instability was more frequently observed in the colonic mucosal lining than in blood serum (p<0.05). We have carried out analysis of the MSI occurrence frequency in colonic tissue depending on the EC phenotypic traits and risk factors. The obtained data on the MSI disorder occurrence frequency in colonic tissue in case of EC depending on the endometrial carcinoma risk factors demonstrated correlation with the majority of criteria, thus verifying the literature data on the presence of common pathogenetic mechanisms in case of EC and colon cancer. Conclusions. 1. MSI disorders in the colonic mucosal lining and blood serum are more frequently observed in case of EC MSI + phenotype. 2. Similarity of pathogenesis in terms of EC and colon cancer is affected by similar phenotypic traits of patients as well as by MSI development.